Application Of The Law To Outsourced Workers The Impact Of The Main Types Of Work (Core Business) To Establish Protection Laws Against Workers/Laborers - Theresia Tri Widyaningsih; Didik Suahriyanto; Ismail (Riviera Publishing, 2025)
Labor issues in Indonesia, including outsourcing, have become a primary concern for stakeholders, including individuals, communities, and companies. Outsourced workers are employees assigned to another company under a specific agreement. Law Number 13 of 2003 on Manpower and Law Number 6 of 2023 on Job Creation serve as the legal basis for regulating this employment relationship. This study aims to analyze the legal protection of outsourced workers using a comparative law approach, legislative analysis, and case studies. The findings indicate that despite existing regulations ensuring legal protection for outsourced workers, legal loopholes still exist, potentially disadvantaging workers, particularly in terms of social security and job stability. The government has a responsibility to ensure the effective implementation of labor laws to protect workers' welfare. Key employment instruments, such as Fixed-Term Employment Agreements (PKWT) and Indefinite-Term Employment Agreements (PKWTT), must be aligned with applicable regulations to protect the rights of outsourced workers. Therefore, regulatory evaluation and reinforcement are necessary to establish a fairer labor system for outsourced workers in Indonesia.